The early to middle Eocene transition: an integrated calcareous nannofossil and stable isotope record from the Northwest Atlantic Ocean (IODP Site U1410) - Cappelli, C; Bown, PR; Westerhold, T; Bohaty, SM; Riu, M; Lobba, V; Yamamoto, Y; Agnini, C (American Geophysical Union (AGU), 2019)
The early to middle Eocene is marked by prominent changes in calcareous nannofossil assemblages coinciding both with long‐term climate changes and modification of the North Atlantic deep‐ocean circulation. In order to assess the impact of Eocene climate change on surface‐water environmental conditions of the Northwest Atlantic, we developed calcareous nannoplankton assemblage data and bulk stable isotope records (δ18O and δ13C) across an early to middle Eocene interval (~52–43 Ma) at IODP Site U1410 (Southeast Newfoundland Ridge, ~41°N). At this site, early Eocene sediments are pelagic nannofossil chalk, whereas middle Eocene deposits occur as clay‐rich drift sediments reflecting the progressive influence of northern‐sourced deep currents. Between the end of Early Eocene Climatic Optimum and the Ypresian/Lutetian boundary, calcareous nannofossils switched from an assemblage mainly composed of warm‐water and oligotrophic taxa (Zygrhablithus, Discoaster, Sphenolithus, Coccolithus) to one dominated by the more temperate and eutrophic reticulofenestrids. The most prominent period of accelerated assemblage change occurred during a ~2 Myr phase of relatively high bulk δ18O values possibly related to the post‐EECO cooling. Although the dominance of reticulofenestrids persisted unvaried throughout the middle Eocene interval, early Lutetian (~47.4 to 47 Ma) stable isotope records indicate a reversal in the paleoenvironmetal trends suggesting a potential restoration of warmer conditions. Importantly, our data indicate that the ~2 Myr‐interval immediately following the EECO was crucial in establishing the modern calcareous nannofossil assemblage structure and also reveal that the establishment of Reticulofenestra‐dominated assemblage occurred prior to the onset of persistent deep‐current system in the Northwest Atlantic.